Cervantes y la novela moderna: Literatura experimental y realismo en el Quijote. - ARDILA, J. A. GARRIDO (Cervantes)
Don Quixote is universally regarded as an emblematic text in the history of the novel. Yet while some scholars have argued that it is a modern novel in its own right and not a romance, others have objected to this theory. When considering the extent to which Don Quixote can or cannot be regarded a modern novel, the question of realism has dominated scholarly research. This article questions the validity of applying Auerbachs theories on realism to the study of Don Quixote. It argues that whilst realism in Don Quixote may not match the models of nineteenth-century French naturalist novelists, it does prefigure the form of realism later developed in the modernist novel. The article also reviews the textual evidence that highlights the fact that Cervantes was consciously and wilfully experimenting with the concept realism with the purpose of writing a prose fiction that departed from the romance.